Effect of argon gas environment on high temperature sliding wear characteristics of NiCrBSi laser clad. (2023) - Jaiswal, Abhimanyu Kumar; Govande, Akshay R.; Uday Venkat Kiran, K.; Ratna Sunil, B.; Dumpala, Ravikumar
Abstract: The martensitic stainless steels find extensive application in steam turbine blades, marine turbine blades, compressor blades etc. due to the optimum combination of strength and corrosion resistance. NiCrBSi alloy has been coated on AISI410 samples by laser cladding process. The tribological characteristics of the coated specimen were investigated against the WC-Co counter ball at 300 °C in the air and argon environments at 12.8 cm/s and 19.2 cm/s sliding velocities. The coated specimen was probed using XRD and scanning electron microscopy. In the argon environment, the wear loss was decreased by 36.84 % and 35.29 % for the sliding velocities of 12.8 cm/s and 19.2 cm/s, respectively, compared with the air environment. Irrespective of the sliding environment, a low wear rate and relatively stable friction curve were observed at higher sliding velocity, i.e., 19.2 cm/s compared to 12.8 cm/s. Oxidation played a major role in the wear loss of the coatings at high temperatures in the air environment, which decreased with the argon gas environment.